Densification kinetics of nanocrystalline zirconia powder using microwave and spark plasma sintering—a comparative study - Vasylkiv, Oleg (2013)
Two-stage densification process of nanosized 3 mol% yttria-stabilized zirconia (3Y-SZ) polycrystalline compacts during consolidation via microwave and spark-plasma sintering have been observed. The values of activation energies obtained for microwave and spark-plasma sintering 260–275 kJ·mol−1 are quite similar to that of conventional sintering of zirconia, suggesting that densification during initial stage is controlled by the grain-boundary diffusion mechanism. The sintering behavior during microwave sintering was significantly affected by preliminary pressing conditions, as the surface diffusion mechanism (230 kJ·mol−1) is active in case of cold-isostatic pressing procedure was applied.